MEDICAL-SOCIAL EXPERTISE AND THE RIGHTS OF PERSONS WITH DISABILITIES - Sardor Djalilov (Web of Journals Publishing, 2024)
This article presents the concept of persons with disabilities and their socio-medical expertise, content, legal framework, covered in national legislation. The article will put forward ideas about the specifics of social expertise, about the implementation specialists and its standards, about the aspects that are practically noteworthy.
Keywords: persons with disabilities and their medical and social examination, disability, medical and social Examination Commission, child with disabilities, criteria for determining disability.